PENGARUH KEPEPMIMPINAN GURU DAN KEMAMPUAN BERKOMUNIKASI GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X DI SMA NEGERI 1 SIANTAR T.A. 2023/2024 - Wynda Aysah Febyola Sinaga; Anggun Tiur Ida Sinaga; Tumpal Manahara Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to gain knowledge about how much influence teacher leadership and teacher communication skills have on student learning motivation in class X economics subjects at SMA Negeri 1 Siantar T.A. 2023/2024.This research is quantitative in type. The sampling technique used a non-probability sampling technique of 70 respondents. Data collection techniques use questionnaires. Instrument testing uses normality tests and reliability tests. The data analysis technique uses classic assumption tests, namely normality test, multicollinearity test, heteroscedasticity test and hypothesis testing, namely multiple linear regression analysis, t-test, f-test and coefficient of determination.Data from research and management of partial test data (t-test) shows that the variable The variable Simultaneous test data management (f-test) shows that F_count is 7.555 > F_table is 3.132 so it can be concluded that teacher leadership and teacher communication skills affect student learning motivation.